On effecting averages nad changes of scale via weighting functions (Archives of Mechanics - Test, 1998)
Weighting functions can be used to derive continuum equations of balance from molecular considerations, and to obtain equations governing fluid flow through porous media. The methodology of such (scale-dependent) averaging is outlined, and physical implications of specific choices of weighting function are discussed.